Design of Security Surveillance and Automatic Water System for Agriculture - Kethineni, Keerthi; Pradeepini, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As automation technology progresses, life becomes simpler and easier in every manner. Automatic systems outnumber manual methods in today’s world. The automatic system is a developing system of daily objects, ranging from industrial machines to consumer items that can execute duties. The same automation when introduced in agriculture activities will helps farmers in getting good crop. The farmer’s dependency on the seasons reduces productivity and constitutes a barrier to the achievement of the food self-sufficiency strategy. Some framers who are involved in mango, guava farming has theft of crop. To solve the problem, an agricultural instrument based on information and communication technologies is required. The goal of this work was to create a programmable microcontroller chip that could regulate irrigation autonomously and also provide security by capturing and storing the data of the persons visiting the filed. An arduino microcontroller is programmed to sensor the moisture level of plants at a specific point in time; if the moisture content is less than a predetermined threshold based on the specific plant’s water requirement, the necessary amount of water is delivered until it passes the threshold. Farmers did not have to irrigate their crops by hand and can also check the saved data of on filed trespassers, this helps farmers to identify the persons in case of crop theft.